Determinação da força de adesão entre partícula e superfícies rugosas através da técnica centrífuga - Petean, Paula Garcia da Costa (Universidade Federal de São Carlos, 2014)
Adhesion between powders and surfaces plays an important role in various technological areas and processes, such as paste drying operations, fluidization of fine particles, microencapsulation, xerography and in food and pharmaceutical processes. Adhesion of small particles to solid surfaces is a phenomenon closely associated with industrial hygiene and air pollution studies. The centrifuge technique to determine adhesion force is based on the detachment of particles from a substrate surface due to centrifugal force. In this technique, a substrate with particles deposited on its surface is rotated at successively increasing speeds, and after each rotation at a given speed, the number of particles remaining on the surface is determined. This technique uses imaging analysis to determine the number of adhered particles on the proof disk surface before and after each centrifugation. After applying a specific press-on, images of the substrates containing particles from the pulverized materials were taken by optical microscope Olympus BX60 (Olympus Co. Tokyo Japan and processed by an image analyzer (Image-Pro Plus 7.0).The results were treated statistically to obtain the mean particle adhesive force. The powder used was a polydisperse sample of microcrystalline cellulose (ρ=1.62 kg m−3). The materials used as substrates were a membrane of cellulose ester 0.2 μm of porosity, brand Shleicher & Shuell - Filtration Life Science, and a compressed particulate (tablets) made of microcrystalline cellulose (Sigma-Aldrich). A microcentrifuge that reached a maximum rotation speed of 14000 rpm which contained specially designed centrifuge tubes was used in the adhesion force measurements. Compression speeds (presson) were applied to each of the experimental runs at 1000, 2000 and 5000 rpm. To detach the particles from the substrate surface, eight cleaning speeds (spin-off) were used. Detachment was done at the centrifugal speeds of: 1000, 3000, 5000, 7000, 9000, 11000, 13000, and 14000 rpm for 1 min. Five particle diameter sizes were studied: 9 15, 15.1 22, 22.1 30, 30.1 42, and 42.1 60 μm. It was observed that the adhesion force increases linearly with the particle diameter, within the range studied and that increased compression speed has an influence on the process of particles detaching. It was possible to obtain a relationship between the adhesion force and diameter of the particles adhered to substrates analyzed The adhesion force experimental results and the adhesion force theoretical values using the models proposed by Derjaguin, Muller and Toporov (DMT) and Johnson, Kendall and Roberts (JKR) were compared. Although the JKR Model was the closest one to the experimental results, the adhesion force theoretical values were far higher than the experimental values. Finally a correction constant (kc) was proposed in order to correlate the theoretical values of adhesion force to the experimental values.
Keywords: Força de adesão; Técnica centrífuga; Superfície rugosa; Force of adhesion; Centrifugal technique; Surface rough; ENGENHARIAS::ENGENHARIA QUIMICA